The Relationship between (Protestant) Christianity and the Environment is Ambivalent - Jochemsen, Henk (Philosophia reformata, 2018)
In his contribution to this special issue, Michael Northcott argues that there is a historic association between Protestant cultures and the origins of environmentalism. It seems to me, however, that the connection between Protestantism and environmentalism is more complicated and ambivalent than the positive relation he highlights. In this paper, I will problematize that relation on the basis of various theoretical and empirical contributions in the literature on religion and environmentalism. Different positions in this regard within Protestantism will be identified and related to theological positions and the historic impact of Protestantism on culture. In the final section, the impact of environmental degradation on the (global) poor will be highlighted, which leads to the identification of a tension between an orthodox/evangelical Protestant stance towards the poor and towards the environment.